2012
DOI: 10.22610/imbr.v4i1.958
|View full text |Cite
|
Sign up to set email alerts
|

Training & Development Practices in National Bank of Pakistan

Abstract: The purpose of this study is to explore the training & development practices in National Bank of Pakistan (NBP). Different levels of officers are providing training & development opportunities in NBP. Data collected from different staff colleges of NBP. Result of this study shows, bank is providing training & development opportunities to its employees, but there is still gap which should be addressed. Training need analysis is not sufficient. Most of the trainers belong to operational background an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The forms include formal education, coaching, mentoring, behavioral modeling, development workshops, on-the-job and off-the-job training (Imran & Tanveer, 2015). Employee training and development result in their higher qualifications and efficiency (Bataineh, 2014), and organizational development (Vinesh, 2014), therefore, it is in the interest of the organization itself (Qayyum et al, 2012). It influences the creation of knowledge and organizational competences, leading increased organizational innovativeness (Marimuthu et al, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The forms include formal education, coaching, mentoring, behavioral modeling, development workshops, on-the-job and off-the-job training (Imran & Tanveer, 2015). Employee training and development result in their higher qualifications and efficiency (Bataineh, 2014), and organizational development (Vinesh, 2014), therefore, it is in the interest of the organization itself (Qayyum et al, 2012). It influences the creation of knowledge and organizational competences, leading increased organizational innovativeness (Marimuthu et al, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Similar researches advocated that training and development (T&D) helps employees to enhance their current skills to advance their performance, build creativity and confidence, and help them to be highly effective in the job. Therefore, T&D not only prepares employees for the next ladder of career but also strengthens their spirit of owning the job, developing cognitive competencies, giving work freedom, and adopting new knowledge in the workplace (Jyoti & Bhau, 2015;Malik et al, 2020;Nauman et al, 2020;Qayyum et al, 2012). Conversely, Awang et al (2010) contested that skill and knowledge may be enhanced by training.…”
Section: Factors Of Employee Performancementioning
confidence: 99%
“…From the early stage of the 21st century, we found that a remarkable flow surrounded by the businesses to draw and keep hold of the endowment. This is very much exhibited due to globalization, technological development (Allen, 2010), and in particular be augmented contests within the market economy and international market (Qayyum, Sharif, Ahmad, Khan, & Rehman, 2012;Kumpikaite & Sakalas, 2011). The demands of the human resources are provided with an uninterrupted knowledge acquisition feeling to keep themselves on the pathway with the organizational goals.…”
Section: Literature Reviewmentioning
confidence: 99%